METHODOLOGICAL APPROACHES TO THE FORMATION OF PSYCHOLOGICAL READINESS OF ATHLETES IN SHOOTING TO OVERCOMING COMPETITIVE DIFFICULTIES - Дмитриева, Николь (SWorldJournal, 2020)
The aim of the article is to determine the methodological approaches to the formation of psychological readiness of athletes in shooting to overcome competitive difficulties. Shooting is one of the shooting sports in which athletes compete in shooting w